Exploring the Role of Video Games in Reducing Academic Stress among Filipino Students - Lowel L. Urian; Maria Lourdes L. Chavez (Philippine Social Science Journal)
This qualitative study explores how Filipino undergraduate students perceive video games as a coping mechanism for academic stress. It examines student views on video games' benefits, identifies helpful game characteristics, and explores integration into academic routines. Through multiple-case analysis of ten student cases, the research generates individual case reports and a cross-case report. Four prominent themes emerge: video games offer stress relief and relaxation, foster social interaction and community, provide cognitive skill practice and development, and motivate time management. Consistent with prior research, the findings suggest video games can be a valuable resource for managing academic stress.